Forecasting of lentil pulse production: An econometric analysis - Rahman, Niaz Md. Farhat; Baten, Md Azizul; Roy, Ashutosh; Hossain, Md. Monir (AENSI Publisher, 2013)
The paper describes an empirical study of modeling and forecasting time series data of lentil pulse production in Bangladesh. The Box Jenkins ARIMA methodology has been used for forecasting.The diagnostic checking has shown that ARIMA (0, 1, 9) is appropriate.The forecasts from 2011-12 to 2015-16 are calculated based on the selected model.These forecasts would be helpful for the policy makers to foresee ahead of time the future requirements of grain storage import and/or export and adopt appropriate measures in this regard.